Plasma-grafted amidoxime/metal–organic framework composites for the selective sequestration of U(vi). Issue 8 (24th July 2018) - Li, Fengbo; Li, Xiaoyu; Cui, Pu; Sun, Yubing
Abstract : The selective sequestration mechanism of U(vi ) by metal–organic framework supported amidoxime (AO/MOF) composites has been demonstrated by batch, XPS and EXAFS analyses. Abstract : The selective sequestration mechanism of U(vi ) by metal–organic framework supported amidoxime (AO/MOF) composites has been demonstrated by batch, XPS and EXAFS analyses. The results of this characterization showed that the as-prepared AO/MOF composites displayed an abundance of nitrogen- and oxygen-bearing functional groups. The batch experiments showed that the maximum U(vi ) adsorption capacity of the AO/MOF composites at pH 7.0 (454.55 mg g −1 by fitting isotherm data with the Langmuir model) was remarkably higher than that of other heavy metals ( e.g., 54, 62, 25 and 68 mg g −1 for Ca(ii ), Mg(ii ), Sr(ii ) and Na(i ), respectively). In addition, the AO/MOF composites could extract 2.74 mg g −1 U(vi ) from Huanghai seawater within 90 min, revealing that the AO/MOF composites presented highly selective adsorption and a rapid enrichment rate for U(vi ) from seawater. XPS analysis indicated that the highly effective adsorption of AO/MOF composites was attributed to the surface functional groups. According to the fitting of the EXAFS data, the occurrence of a U–C shell for the U-loaded AO/MOF at pH 3.0 revealed inner-sphere surface complexation at low pH. These findings elucidated that AO/MOF composites can be regarded an excellent adsorbents for highly effective removal of U(vi ) from aqueous solution and selective sequestration of U(vi ) from seawater, which are crucial for realizing the development of sustainable nuclear energy.